Pandemic as Pretext: The Implications of Global Cataclysms in Don DeLillo’s The Silence and Slavoj Žižek’s Writings on Covid-19 - Alicja Piechucka (European Journal of American Studies)
The article focuses on Don DeLillo’s latest novel, The Silence, which is analyzed and interpreted in light of Slavoj Žižek’s writings collected in Pandemic!: COVID-19 Shakes the World and Pandemic!2: Chronicles of a Time Lost. While all three works were published in 2020, only the last two deal explicitly with the coronavirus pandemic. In The Silence, DeLillo does not mention the pandemic at all; he does, however, refer to it directly in a short essay which was added to the novel’s later editions. This does not change the fact that the atypical situation in which DeLillo’s characters find themselves, though caused by factors of a technical rather than sanitary nature, bears numerous resemblances to what people all over the globe experienced during the Covid-19 pandemic. The aim of the study is to read The Silence through the lens of Žižek’s reflections and thereby to examine the political, sociocultural, technological and human implications of global cataclysms. My argument is that for both the American novelist and the Slovenian philosopher, worldwide disasters such as the blackout depicted in The Silence or the 2020 pandemic are merely a pretext for delving into the condition of the modern world, with particular emphasis on how twenty-first-century reality is affected by globalization, science, technology, war and environmental degradation. DeLillo’s novel is more of a meditation while Žižek’s collection of essays may be seen as a call to action. Nevertheless, both are statements on a humanity in crisis, disoriented, fragile and helpless, living in times which are, paradoxically, uncertain and even paranoia-inducing despite the unprecedented scale of scientific and technological progress.